A Legal Study of Electronic Deed On Purchase and Sale Land During The Covid 19 Pandemic - Mufarrijul Ikhwan; Rina Yulianti (Jurnal Dinamika Hukum, 2021)
--During pandemic time, land sale and purchase transaction activity is still likely conducted; therefore, to replace and to minimize face-to-face mobility among the parties, digital transaction policy should be provided through cyber notary. The objective of paper was to find out the legal framework for the certainty and validity of agreement made by notary in electronic procedure as robust evidence in land sale and purchase transaction during covid-19 pandemic time. This paper employed juridical normative research method with statute approach and conceptual approaches to study electronic deed likely made by notary during covid-19 pandemic time. Electronic land sale and purchase deed made during Covid-19 pandemic time is legitimate based on lex specialist derogate legi generally principle, the enactment of health quarantine regulation. Juridical construction to give law protection to cyber notary service, particularly land sale and purchase deed development in Indonesia, can be provided through policy issued by Ministry of Agrarian Affairs and Spatial Planning/National Land Agency through referring to the provisions about Notary (PPAT)’s authority in Notary Position Law, Governmental Administration Law, Archive Law, and Information and Electronic Transaction Law.   Keywords- Covid-19, electronic deed, sale and purchase, land